Analisis Pengaruh Pajak Daerah, Retribusi Daerah Terhadap Tenaga Kerja Dan Pertumbuhan Ekonomi Di Kota Palangka Raya Provinsi Kalimantan Tengah - Dewi, Ju Kumala; Sri Budhi, Made Kembar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.06.TAHUN 2018, 2018)
This study aims to analyze the direct influence of local taxes and levies on the absorption of labor, to analyze the direct influence of local taxes, levies, employment to economic growth and to analyze the indirect effect of local taxes, regional levies on economic growth through employment. The research sample used in this research is Kota Palangka Raya. Secondary data used in this study were obtained from the Revenue Service, employment data obtained from the Office of Manpower and Transmigration as well as data on economic growth based on 2000 constant prices obtained from the Central Bureau of Statistics in Kota Palangka Raya from 1996-2016.Testing data in this study using path analysis techniques with the help of SPSS 21 applications. The results of testing direct influence in this study indicate 1) Local taxes and user charges affect the workforce ; 2) Local taxes have an effect on economic growth while regional levy has no effect on labor; and 3) The result of indirect effect test indicates that the workforce is not able to mediate local tax variables and regional levies on economic growth.